Edukasi Hidroponik Berdaya Berbasis Webinar pada Kondisi Pandemi Covid-19 - Ariesman Ariesman; Aswar Aswar; M. Amirullah (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2022)
The increasingly widespread spread of Covid-19 and the increasing number of victims who have died from the virus have caused more activities to be carried out at home. Therefore, the government made a policy by implementing Large-Scale Social Restrictions (PSBB), Lockdown as an effort to prevent the spread of the virus. However, the government has also made an offer to do Work from Home (WFH) so that productive activities can continue amid the Covid-19 pandemic. Among the positive and useful activities, such as holding virtual-based hydroponic training for the community. The hydroponic training method is carried out boldly through zoom webinars, the activities are conceptualized and arranged systematically, it is hoped that the participants can master the basic and simple techniques to start hydroponics at home and can take advantage of limited land. Based on the results of this virtual-based hydroponic training it was found that the participants seemed enthusiastic and responded very well to the training material, indicated by the number of questions and the number of participants who attended, some of whom even planned to directly hold hydroponic training. Because the training material presented is quite light and easily understood by the participants. In addition, this training is in accordance with the principles of hydroponic beginners, simple, and the use of familiar tools around us.